2022
DOI: 10.20961/carakatani.v38i1.62652
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Drought-Tolerant Impatiens Genotypes by Using Water Stress Treatment

Abstract: The drought-tolerant Impatiens genotypes are known for their resistance to limited or stressed water. The study aimed to identify drought-tolerance of Impatiens clones. The experiment used a split-plot design replicated three times, with the water stress treatment as the main plot and Impatiens clones as subplots. The main plot consists of 100% and 60% of field capacity. The subplots consist of five Impatiens clones, 17.12; 12; 33.3; 40 B and Impatiens cv of Impala Agrihorti as a control. The results showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Environmental observations during the rooted cutting plant growth showed that the average temperature, relative humidity, and light intensity were 26.38 °C, 81.17% and 7,388 Lux respectively as shown in Table 1. According to a previous study, the Impatiens juvenile requires temperatures in the range of 21.50 to 26.50 °C (Shintiavira et al, 2023). This indicates that the Impatiens were provided with optimal conditions in this study for their growth and development.…”
Section: Environmentmentioning
confidence: 61%
See 1 more Smart Citation
“…Environmental observations during the rooted cutting plant growth showed that the average temperature, relative humidity, and light intensity were 26.38 °C, 81.17% and 7,388 Lux respectively as shown in Table 1. According to a previous study, the Impatiens juvenile requires temperatures in the range of 21.50 to 26.50 °C (Shintiavira et al, 2023). This indicates that the Impatiens were provided with optimal conditions in this study for their growth and development.…”
Section: Environmentmentioning
confidence: 61%
“…Light intensity was measured above the plant canopy using a lux meter, while air temperature and humidity were recorded with a thermohygrometer. The measurements were carried out in the morning (09.00 a.m.), afternoon (12.00 p.m.) and evening (03.00 p.m.) (Shintiavira et al, 2023). Before planting, the pH values for the growth medium were determined by combining 10 g medium with 50 ml water, agitating for 30 minutes and leaving it standing for 24 hours.…”
Section: Measurement Of Environment and Growth Medium Propertiesmentioning
confidence: 99%
“…Water in the soil fills the existing soil pores. The more pores in the soil, the more water will be available; otherwise, the more pores in the soil will cause the soil's weight to be light [43]. The higher the value of soil content weight, the smaller the total soil pore space, so that the proportion of pore space for water is also less, while the smaller the value of soil content weight, the higher the value of soil pore space, so that the water capacity in the soil will also increase [44].…”
Section: Limiting Factors Of Soil Water Retentionmentioning
confidence: 99%